Differences in gene expression profiles in early and late stage rhodesiense HAT individuals in Malawi - Nambala, Peter; Mulindwa, Julius; Harry, Noyes; Alibu, Vincent Pius; Nerima, Barbara; Namulondo, Joyce; Nyangiri, Oscar; Matovu, Enock; Annette, MacLeod; Musaya, Janelisa (PLoS neglected tropical diseases, 2023)
T. b. rhodesiense is the causative agent of Rhodesian human African trypanosomiasis (r-HAT) in Malawi. Clinical presentation of r-HAT in Malawi varies between foci and differs from East African HAT clinical phenotypes. The purpose of this study was to gain more insights into the transcriptomic profiles of patients with early stage 1 and late stage 2 HAT disease in Malawi. Whole blood from individuals infected with T. b. rhodesiense was used for RNA-Seq. Control samples were from healthy trypanosome negative individuals matched on sex, age range, and disease foci. Illumina sequence FASTQ reads were aligned to the GRCh38 release 84 human genome sequence using HiSat2 and differential analysis was done in R Studio using the DESeq2 package. XGR, ExpressAnalyst and InnateDB algorithms were used for functional annotation and gene enrichment analysis of significant differentially expressed genes. RNA-seq was done on 23 r-HAT case samples and 28 healthy controls with 7 controls excluded for downstream analysis as outliers. A total of 4519 genes were significant differentially expressed (p adjusted <0.05) in individuals with early stage 1 r-HAT disease (n = 12) and 1824 genes in individuals with late stage 2 r-HAT disease (n = 11) compared to controls. Enrichment of innate immune response genes through neutrophil activation was identified in individuals with both early and late stages of the disease. Additionally, lipid metabolism genes were enriched in late stage 2 disease. We further identified uniquely upregulated genes (log2 Fold Change 1.4–2.0) in stage 1 (ZNF354C) and stage 2 (TCN1 and MAGI3) blood. Our data add to the current understanding of the human transcriptome profiles during T. b. rhodesiense infection. We further identified biological pathways and transcripts enriched than were enriched during stage 1 and stage 2 r-HAT. Lastly, we have identified transcripts which should be explored in future research whether they have potential of being used in combination with other markers for staging or r-HAT.